2022
DOI: 10.3389/fnut.2022.913155
|View full text |Cite
|
Sign up to set email alerts
|

Causal Relationship of Genetically Predicted Serum Micronutrients Levels With Sarcopenia: A Mendelian Randomization Study

Abstract: ObjectivesPrevious observational studies have suggested associations between concentrations of several circulating micronutrients and sarcopenia. However, the causality inferred from those studies was subjected to residual confounding and reverse causation. Therefore, we aimed to examine the causal effects of the levels of genetically predicted serum micronutrients on sarcopenia.MethodsSingle nucleotide polymorphisms (SNPs) were chosen from large-scale genome-wide association studies of participants only with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 56 publications
1
10
0
Order By: Relevance
“…Our study revealed that the in uence of 3-dehydrocarnitine and hyodeoxycholate on grip strength disappeared after correcting for obesity and type 2 diabetes. A recent MR study also analyzed the causal relationship between blood metabolites and grip strength, and the results were similar to our study [33]. Univariate MR analysis revealed that 3-dehydrocarnitine and hyodeoxycholate were causally related to grip strength, but a previous study did not perform multivariate MR analysis to correct for the impact of obesity and diabetes.…”
Section: Discussionsupporting
confidence: 85%
“…Our study revealed that the in uence of 3-dehydrocarnitine and hyodeoxycholate on grip strength disappeared after correcting for obesity and type 2 diabetes. A recent MR study also analyzed the causal relationship between blood metabolites and grip strength, and the results were similar to our study [33]. Univariate MR analysis revealed that 3-dehydrocarnitine and hyodeoxycholate were causally related to grip strength, but a previous study did not perform multivariate MR analysis to correct for the impact of obesity and diabetes.…”
Section: Discussionsupporting
confidence: 85%
“…The association of vitamin D levels with sarcopenia or its related indices has previously been investigated in 4 MR studies . Three of them used the standard MR analysis .…”
Section: Discussionmentioning
confidence: 99%
“…The association of vitamin D levels with sarcopenia or its related indices has previously been investigated in 4 MR studies. 37 , 38 , 39 , 40 Three of them used the standard MR analysis. 38 , 39 , 40 One study reported a null association between 25(OH)D and sarcopenia risk, 38 and the other 2 showed a beneficial effect of 25(OH)D on grip strength 39 and lean mass.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Likewise, branched-chain amino acids, polyunsaturated fatty acids, selenium, vitamin D, and zinc can reduce oxidative stress, support mitochondrial homeostasis, and mitigate low-grade inflammation, thus suggesting their potential roles in the treatment of sarcopenia ( 128 ). To the contrary, however, a Mendelian randomization analysis shows little effect from these nutrients with the exception of a genetically high concentration of serum iron, which increased sarcopenia risk ( 129 ).…”
Section: Nutritional Therapy In Patients With Acute Covid-19 T2d and ...mentioning
confidence: 99%